Optimalisasi Penyelesaian Perkara Tindak Pidana Pencurian Yang Dilakukan oleh Anak Melalui Diversi - Prasetiyo, Rudi; Sudarmanto, Kukuh; Sukarna, Kadi; Ridwan, Mukhlis (Journal Juridisch, 2024)
The study aims to analyze the optimization of the settlement of theft criminal cases committed by children in a diverse way. Children, as part of the future of the nation, have the right to grow and develop optimally, both physically and mentally, as well as socially and morally. Children involved in criminal acts such as theft often come from an under-supported family background, a lack of adequate education, or a poor social environment. Handling criminal cases involving children requires a different approach than adult perpetrators. Diversion, as one of the forms of settlement of criminal cases of children outside formal judicial proceedings, has been regulated in Act No. 11 of 2012 on the Child Criminal Justice System (SPPA). The urgency of this research lies in the need to find an effective solution to dealing with the crime of theft by children through diversified mechanisms. This method of investigation is juridic normative with supported secondary data as primary data and data. By maximizing diversification, it is expected to provide better protection for children facing the law, reduce the negative effects of formal judicial processes, and encourage children to return to society. This research offers some significant aspects of innovation. First, the study developed a diversified optimization strategy model that had not been comprehensively outlined in previous research. Second, it used a multidisciplinary approach that integrated legal, psychological, and sociological perspectives into its analysis. Third, the research identified key factors that influenced the success of diversion implementation in cases of child theft, which could be a reference for future public policy.